Peran Kepala Desa dalam melaksanaan pembangunan di Desa Empakan Kayan Hulu Kabupaten Sintang. - Nikodimus, Nikodimus (Universitas Kapuas Sintang, 2026)
Abstrak This study aims to identify and analyze the role of the village head in implementing development in Empakan Village, Kayan Hulu District, Sintang Regency. This study uses a qualitative approach with descriptive methods. Data collection techniques were conducted through in-depth interviews, observation, and documentation. Informants in this study consisted of the village head, village officials, the Village Consultative Body, community leaders, and the Empakan Village community. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing and verification. The research results indicate that the Village Head's role in village development planning has been quite effective through the implementation of village deliberations involving various community elements. In implementing development, the Village Head acts as the coordinator and person responsible for development activities, both physical and non-physical. Village development is monitored through direct monitoring and collaboration with the Village Consultative Body, although implementation is not yet fully optimal. Obstacles faced in implementing village development include limited human resources within the village apparatus, budget constraints, geographical conditions, and uneven community participation. Based on these research results, it can be concluded that the Village Head's role in implementing development in Empakan Village, Kayan Hulu District, Sintang Regency has been quite effective, but still needs improvement, especially in the areas of oversight and community empowerment to achieve sustainable village development